Contexto deposicional da sequência Balbuena III (Maastrichtiano/ Daniano) da formação Yacoraite na sub-bacia metán-alemania, na região de Salta, Argentina - Oliveira, Eduardo Roemers de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Salta Basin is located in the northwest of Argentina and its origin is related to an intracontinental rift which was formed during the Cretaceous and early Paleogene. It is subdivided into four sub-basins (Lomas de Olmedo - east; Sey - west; Tres Cruces - north; and Metán-Alemania - south) that were filled by sediments from the Pirgua (synrift phase) and Balbuena (sag phase) supersequences. The sedimentary section that forms the sag phase is divided into four sequences: Balbuena I, II, III and IV, from bottom to top. This research covers the sedimentological and stratigraphical outcrops characterization of the Balbuena III Sequence (Maastrichtian/Danian) from Yacoraite Fm., in the Metán-Alemania sub-basin, Cabra Corral dam region, district of Coronel Moldes, Argentina. The data have been collected from the survey of 14 vertical stratigraphic sections measured in these outcrops at a 1:40 scale, where spectral gamma-ray logs have been acquired and samples for sedimentological analysis have been collected. Data analysis has shown that Balbuena III Sequence consists of carbonate, siliciclastic and mixed facies which have been deposited in a lacustrine environment. The carbonate facies are formed by oolitic/bioclastic grainstones, oolitic/bioclastic packstones, bioclastic rudstones and floatstones, carbonate mudstones, laminites and stromatolites.The siliciclastic facies correspond to very fine wavy sandstones, siltstones and mudstones.The lithofacies of mixed deposition (with carbonate and siliciclastic components) consist of hybrid sandstones and marls.The identified lithofacies have been grouped into four facies associations, which from field observations, could be grouped into two ideal vertical successions of facies (elementary sequences). The observed cycles have been ranked in sequences of medium and high frequencies and could be traced for tens of kilometers in the basin. From the understanding of the distribution of...

A Bacia de Salta localiza-se no noroeste argentino e sua origem está relacionada a um rifte intracontinental, formado durante o Cretáceo e início do Paleógeno. Subdivide-se em quatro sub-bacias (Lomas de Olmedo a leste; Sey a oeste; Tres Cruces a norte; e Metán-Alemania a sul) que foram preenchidas por sedimentos das supersequências Pirgua (fase sin-rifte) e Balbuena (fase sag). A seção sedimentar que compõe a fase sag é dividida em quatro sequências: Balbuena I, II, III e IV, da base para o topo. O presente estudo aborda a caracterização faciológica e estratigráfica com base em afloramentos da Sequência Balbuena III (Maastrichtiano/Daniano) da Fm. Yacoraite, na Sub-bacia Metán-Alemania, região do dique Cabra Corral, distrito de Coronel Moldes, Argentina. Os dados foram obtidos no levantamento de 14 seções estratigráficas verticais na escala 1:40, nas quais foram adquiridos perfis de raios gama espectral e realizada coleta de amostras para análises sedimentológicas. A análise faciológica revelou que a Sequência Balbuena III é composta por fácies carbonáticas, siliciclásticas e mistas, depositadas em ambiente lacustre. As fácies carbonáticas são constituídas por grainstones oolíticos e/ou bioclásticos, packstones oolíticos e/ou bioclásticos, rudstones e floastones bioclásticos, mudstones, laminitos e estromatólitos. As fácies siliciclásticas correspondem a arenitos muito finos ondulados, siltitos e lamitos. As litofácies de deposição mista (com componentes siliciclásticos e carbonáticos) são constituídas por arenitos híbridos e margas. As litofácies identificadas foram agrupadas em quatro associações de fácies, que a partir das observações de campo, resultaram em duas sucessões verticais ideais de fácies (sequências elementares). Tais sucessões foram hierarquizadas em sequências de média e alta frequências e puderam ser rastreadas por dezenas de quilômetros na bacia. A partir do...
Keywords: Sedimentation and deposition; Sedimentação e depósito; Geologia estratigráfica; Lagos - Sedimentos; Petrologia; Facies (Geologia); Argentina